Cynaropicrin attenuates UVB-induced oxidative stress via the AhR–Nrf2–Nqo1 pathway. Issue 2 (16th April 2015) - Takei, Kenjiro; Hashimoto-Hachiya, Akiko; Takahara, Masakazu; Tsuji, Gaku; Nakahara, Takeshi; Furue, Masutaka
Highlights Artichoke is known for its antioxidant and anti-inflammatory activities. Cynaropicrin is a major bioactive phytochemical in the artichoke. Cynaropicrin activates AhR–Nrf2–Nqo1 antioxidant pathway. Antioxidant cynaropicrin attenuates ultraviolet B-induced oxydation in keratinocytes. Antioxidant cynaropicrin potently inhibits the production of IL-6 and TNFα.